Efficacy and safety of a new drug formulation, amoxicillin-clavulanate-cineole, for adult lower respiratory tract infections: a nationwide observational study in Morocco - Benjelloun, Mohamed Chakib; El Achhab, Youness; Nejjari, Chakib; , the ORCA Study Group (Frontiers in Pharmacology, 2025)
BackgroundLower respiratory tract infections (LRTIs) remain significant global health threats, causing substantial morbidity and mortality. The treatment landscape for LRTIs has evolved significantly, presenting increasing challenges due to rising antibiotic resistance and frequent treatment failures. This study aims to examine the real-life efficacy and safety of a new drug formulation, Olipen® (amoxicillin-clavulanate-cineole), in adult patients with LRTIs within the community setting.MethodsThis observational, non-interventional study recruited 936 patients. Olipen® 500 mg (amoxicillin 500 mg, clavulanate 62.5 mg, cineole 100 mg) was administered as two sachets, three times daily, for 7–14 days, as per clinical practice guidelines. The primary outcome focused on the clinical recovery and safety as a secondary outcome.ResultsA total of 936 patients were enrolled in the study at the national level. Nearly all patients (94.9%) achieved clinical recovery. Therapeutic failure was reported in 26 patients (2.8%), while the outcome remained undetermined for 22 patients (2.3%). After 3–4 days of treatment, 57.8% of patients were symptom-free. Radiologically, 81% of patients showed improvement during follow-up. Treatment effectiveness is not affected patient characteristics, whereas chronic cough and dyspnea may hinder clinical recovery in pa-tients with LTRIs. Olipen® was well tolerated, with most of the adverse events reported were considered non-serious and most of them were resolved (87.5%).ConclusionOlipen® was found to be effective and well tolerated in adults with acute exacerbation of chronic bronchitis/COPD, community-acquired pneumonia or superinfection as well as adult patients with pathological lung.